2021
DOI: 10.1002/adem.202100696
|View full text |Cite
|
Sign up to set email alerts
|

Focus on Bioinspired Textured Surfaces toward Fluid Drag Reduction: Recent Progresses and Challenges

Abstract: After a long period of biological evolution, natural creatures will inevitably evolve body surfaces suitable for the living environment. The functions of natural biological surfaces are abundant and powerful, including antiadhesion, self‐cleaning, drag reduction, anti‐icing, wear resistance, and other characteristics. In the context of coping with the energy crisis, inspired by natural biological surface microstructures, researchers explore biomimetic surface microstructures that reduce fluid drag and investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 240 publications
(341 reference statements)
0
19
0
Order By: Relevance
“…Research on surface microstructure drag reduction is no longer limited to continuous and neat ribs with two-dimensional cross sections but gradually becomes intermittent and bifurcated to seek a higher drag reduction rate . Furthermore, some bionic surfaces with three-dimensional raised structures have been found to have drag reduction potential and have been extensively studied . Protrusive surfaces are abundant in nature, in the form of undulating peaks, cone trees, cactus spikes, and small spines on fish skin, which indicate adaptability to realistic operating conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on surface microstructure drag reduction is no longer limited to continuous and neat ribs with two-dimensional cross sections but gradually becomes intermittent and bifurcated to seek a higher drag reduction rate . Furthermore, some bionic surfaces with three-dimensional raised structures have been found to have drag reduction potential and have been extensively studied . Protrusive surfaces are abundant in nature, in the form of undulating peaks, cone trees, cactus spikes, and small spines on fish skin, which indicate adaptability to realistic operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, some bionic surfaces with three-dimensional raised structures have been found to have drag reduction potential and have been extensively studied. 7 Protrusive surfaces are abundant in nature, in the form of undulating peaks, cone trees, cactus spikes, 8 and small spines on fish skin, which indicate adaptability to realistic operating conditions. It is reported that the protruding structure can raise the TBL and reduce the viscous drag, which is beneficial to reducing the drag.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The mucus at the bottom is not easily lost even at high inflow velocities because of the obstruction of the puffer spines. Moreover, the drag reduction function of the puffer spines has been proven. …”
Section: Resultsmentioning
confidence: 97%
“…The surface of marine organisms secretes mucus to cover the whole body, the rough skin of sharks is covered by the shield scale, and covering with an elastic-damping layer is a strategy for dolphins to combat water. The hydrodynamic advantages of the ribs on the shark's bionic drag reduction surface and the ribs embedded in the turbulent boundary layer (TBL) have been fully demonstrated, and their cross sections are regular ravines such as triangles or rectangles, 5 due to the diversion of ribs and the boosting effect of the similar vortex generator shield scales. However, the special structure of the groove also tends to accumulate fouling, leading to clogging and surface performance failure.…”
Section: ■ Introductionmentioning
confidence: 99%